Unravelling the Complexity of Inherited Retinal Dystrophies Molecular Testing: Added Value of Targeted Next-Generation Sequencing. - Bernardis, Isabella; Chiesi, Laura; Tenedini, Elena; Artuso, Lucia; Percesepe, Antonio; Artusi, Valentina; Simone, Maria Luisa; Manfredini, Rossella; Camparini, Monica; Rinaldi, Chiara; Ciardella, Antonio; Graziano, Claudio; et al. (BioMed Research International, 2016)
To assess the clinical utility of targeted Next-Generation Sequencing (NGS) for the diagnosis of Inherited Retinal Dystrophies (IRDs), a total of 109 subjects were enrolled in the study, including 88 IRD affected probands and 21 healthy relatives. Clinical diagnoses included Retinitis Pigmentosa (RP), Leber Congenital Amaurosis (LCA), Stargardt Disease (STGD), Best Macular Dystrophy (BMD), Usher Syndrome (USH), and other IRDs with undefined clinical diagnosis. Participants underwent a complete ophthalmologic examination followed by genetic counseling. A custom AmpliSeq™ panel of 72 IRD-related genes was designed for the analysis and tested using Ion semiconductor Next-Generation Sequencing (NGS). Potential disease-causing mutations were identified in 59.1% of probands, comprising mutations in 16 genes. The highest diagnostic yields were achieved for BMD, LCA, USH, and STGD patients, whereas RP confirmed its high genetic heterogeneity. Causative mutations were identified in 17.6% of probands with undefined diagnosis. Revision of the initial diagnosis was performed for 9.6% of genetically diagnosed patients. This study demonstrates that NGS represents a comprehensive cost-effective approach for IRDs molecular diagnosis. The identification of the genetic alterations underlying the phenotype enabled the clinicians to achieve a more accurate diagnosis. The results emphasize the importance of molecular diagnosis coupled with clinic information to unravel the extensive phenotypic heterogeneity of these diseases.